Performance assessment of intravenous catheters for massive transfusion: A pragmatic in vitro study. Issue 6 (13th April 2021) - Milne, Andrew; Teng, Justin J.; Vargas, Andrew; Markley, John C.; Collins, Adam
Abstract: Background: Rapid infusion of warmed blood products is the cornerstone of trauma resuscitation and treatment of surgical and obstetric massive hemorrhage. Integral to optimizing this delivery is selection of an intravenous (IV) catheter and use of a rapid infusion device (RID). We investigated which IV catheter and RID system enabled the greatest infusion rate of blood products and the governing catheter characteristics. Study Design and Methods: The maximum flow rates of nine IV catheters were measured while infusing a mixture of packed red blood cells and fresh frozen plasma at a 1:1 ratio using a RID with and without a patient line extension. To account for IV catheters that achieved the RID's maximum 1000 ml/min, the conductance of each infusion circuit configuration was calculated. Results: IV catheters of 7‐Fr caliber or higher reached the maximum pressurized flow rate. The 9‐Fr multi‐lumen access catheter (MAC) achieved the greatest conductance, over sevenfold greater than the 18 g peripheral catheter (4.6 vs. 0.6 ml/min/mmHg, p < .001). Conductance was positively correlated with internal radius ( β = 1.098, 95% CI 4.286–5.025, p < .001) and negatively correlated with length ( β = − 0.495, 95% CI −0.007 to 0.005, p < .001). Use of an extension line ( β = − 0.094, 95% CI −0.505 to −0.095, p = .005) was independently associated with reduced conductance in large caliber catheters. Conclusion: Short, large‐diameter catheters provided the greatest infusion rates of massive transfusion blood products for the least pressure. For patients requiring the highest transfusion flow rates, extension tubing should be avoided when possible.